Designing a Security Framework for Mitigating Flaws in Cloud Based Web Hosting for Privacy and Confidentiality Services - Khare, Surbhi; Verma , Vijayant (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The rapid growth in popularity of computing clouds has attracted and allowed intensive processing on resource-constrained client devices. Smart mobiles can install data- and computation-intensive programs thanks to the demand service model utilized by distant data centers Outsourcing personal and sensitive data to far-off data centers, on the other hand, creates significant privacy and security issues. It is necessary to improve the traditional advanced encryption standard (AES) algorithm in order to fulfill the rising security concerns in the cloud. Among the various advantages presented in this research are, for example, increased data security and owner privacy. The encryption speed is increased from 128 to 1000 bits per second with the help of a double round key. There was once a round key that could handle 800 blocks per second. Network trust and resource management may be enhanced while consuming less power and better load balancing by adopting the suggested strategy. In the proposed framework, AES will be utilized with plain text sized at 16, 32, 64, and 128 bytes. The simulation results are shown to show how well the algorithm meets quality standards. The proposed architecture, according to the results, reduces energy use by 14.43%, network utilization by 11.533%, and delay by 15.673%. This new design increases security while also making better use of resources and reducing the amount of time it takes to build new computational cloud services.